Sustainability of the Brazilian Economy Using the System Public Funds Transfers in SICONV - Ilka Massue Sabino Kawashita, Luiz Lustosa Vieira; de Aguiar Neto José Antônio (European Journal of Sustainable Development, 2017)
Decree No. 6,170/2007 regulated agreements, transfer agreements and terms of decentralized execution signed by federal public administration’s organs and entities with organs or, public or private nonprofit entities for the implementation of programs, projects and activities involving the transfer of resources and decentralization of credits arising from the Union’s Fiscal and Social Security Budget; and created the Agreements and Transfer Agreements Management System - SICONV, open to the public, through the Portal of Agreements. SICONV initiated a new era in public management; as it renewed the relationship between Federal Government and its organs; and public and private entities signing agreements, transfer agreements and terms of partnership celebrated with Union’s resources. This initiative automated transfers’ processes, since all procedures are now performed and recorded in this system. SICONV covers all operations of the voluntary transfers life cycle, from the provision of resources to accountability, and it is seamlessly integrated with the main structuring systems of the Federal Government. Thus, SICONV established itself in the Public Administration as a major transformation system that enabled and consolidated changes in many patterns and concepts - currently already established - of how voluntary transfers were executed. Keywords: Information Technology, Government Information Systems, Public Management, Public Administration, Knowledge Management